Correction: Adaptable piezoelectric hemispherical composite strips using a scalable groove technique for a self-powered muscle monitoring system. Issue 6 (29th January 2018) - Rao Alluri, Nagamalleswara; Vivekananthan, Venkateswaran; Chandrasekhar, Arunkumar; Kim, Sang-Jae
Abstract : Correction for 'Adaptable piezoelectric hemispherical composite strips using a scalable groove technique for a self-powered muscle monitoring system' by Nagamalleswara Rao Alluri et al., Nanoscale, 2018, 10, 907–913.